Human group3 innate lymphoid cells express DR3 and respond to TL1A with enhanced IL‐22 production and IL‐2‐dependent proliferation. Issue 8 (22nd June 2015) - Ahn, Yong‐Oon; Weeres, Matthew A.; Neulen, Marie‐Luise; Choi, Jahyang; Kang, Seong‐Ho; Heo, Dae Seog; Bergerson, Rachel; Blazar, Bruce R.; Miller, Jeffrey S.; Verneris, Michael R.
<x xml:space="preserve">Abstract</x> Death receptor 3 (DR3, TNFRSF25) is expressed by activated lymphocytes and signaling by its ligand, TL1A, enhances cytokine expression and proliferation. Recent studies show that DR3 is also present on murine type 2 innate lymphoid cells (ILC2s). Here, we show that DR3 is expressed by IL‐22‐producing human group 3 innate lymphoid cells (ILC3s). Stimulation of ILC3s with exogenous TL1A alone had no impact on cytokine production or proliferation. Addition of TL1A to IL‐1β + IL‐23 significantly enhanced the amount IL‐22 produced by ILC3s as well as the percentage IL‐22‐ and IL‐8‐producing cells. Addition of TL1A to IL‐1β + IL‐23 also augmented ILC3 proliferation. Mechanistically, this occurred through the upregulation of CD25 and responsiveness to IL‐2 stimulation. The combination of TL1A, IL‐1β+ IL‐23, and IL‐2 expanded ILC3s while IL‐1β+ IL‐23 did not increase proliferation above controls. After 2 weeks of expansion, ILC3s maintained their phenotype, transcription factor expression, and function (IL‐22 production). These findings identify DR3 as a costimulatory molecule on ILC3s that could be exploited for ex vivo expansion and clinical use.